ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI KOTA BANJARMASIN - DWI TEGUH APRIANTO (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research proposes about the influence of unemployment rate, PDRB, and education level to poverty level in Banjarmasin city year 2002-2016. Poverty is one of the problems in economic development. Therefore, in this study measure how big the poverty level and the factors that influence it policies to overcome poverty city of Banjarmasin.The scope of this study covers poverty conditions in Banjarmasin City. By analyzing for 15 years. multiple linier regression analysis method. By using R-Square Test (R2), Simultaneous Test (F Test) and Individual Test (t test).Unemployment, PDRB, and education together affect the kemiskunan. The effect of the unemployment rate and the level of education has no significant effect on poverty. While PDRB have a significant effect on poverty in Banjarmasin City. The most dominant factor affecting poverty is PDRB. Keywords : Poverty, Unemployment, PDRB, and Education.